Accuracy of thoracolumbar transpedicular and vertebral body percutaneous screw placement: coupling the Rosa® Spine robot with intraoperative flat-panel CT guidance—a cadaver study. Issue 4 (December 2015) - Lefranc, M.; Peltier, J.
Abstract The primary objective of the present study was to eval uate the accuracy of a new robotic device when coupled with intraoperative flat-panel CT guidance. Screws (D8-S1) were implanted during two separate cadaver sessions by coupling the Rosa® Spine robot with the flat-panel CT device. Of 38 implanted screws, 37 (97.4 %) were fully contained within the pedicle. One screw breached the lateral cortical of one pedicle by <1 mm. The mean ± SD accuracy (relative to pre-operative planning) was 2.05 ± 1.2 mm for the screw head, 1.65 ± 1.11 for the middle of the pedicle and 1.57 ± 1.01 for the screw tip. When coupled with intraoperative flat-panel CT guidance, the Rosa® Spine robot appears to be accurate in placing pedicle screws within both pedicles and the vertebral body. Large clinical studies are mandatory to confirm this preliminary cadaveric report.